Prevention of Sexual Violence at an Early Age: The Effectiveness of Educational Videos for Kindergarten Children - Isabella Hasiana (Early Childhood Development Gazette, 2024)
This study aims to determine the level of knowledge and effectiveness of the use of educational videos as an effort to prevent sexual violence in kindergarten group B children as many as 38 students. Acts of violence against children are a very serious problem and have consequences for victims and society. Every child has the right to enjoy a safe childhood and a life free from violence. Providing sexual education from an early age is important to encourage healthy child development both physically and mentally or psychologically. The approach in this study uses a quantitative method with a pre-experimental research design, namely one group pretest and posttest. The results of the study showed that there was an increase in knowledge and awareness of violence in children. Children have knowledge of sexual violence and are able to defend themselves when they are in situations that make them feel uncomfortable. The results are expected to provide insight into the effectiveness of educational videos in increasing children's knowledge and awareness of sexual violence, as well as emphasizing the importance of sexual education from an early age to prevent violence against children.